IMPROVING STATISTICS LEARNING OUTCOMES THROUGH DEEP LEARNING AND TARL APPROACHES IN GRADE X - Sukmananda, Indah Susitya; Sunismi, Sunismi; Trisniwati, Retno (Universitas Sembilanbelas November Kolaka, 2025)
This study aims to improve students’ learning outcomes in statisticsusing a digital-based approach. The approach integrates DeepLearning principles and the Teaching at the Right Level (TaRL)framework. The research was conducted as a Classroom ActionResearch (CAR) in two cycles involving Grade X students at SMAN 3Malang. Data were collected using pre-tests and post-tests to measurechanges in students' performance. The results showed an increase instudents’ average learning outcomes: from 35.15% in the initialcondition to 54% in Cycle I, and further to 88.4% in Cycle II. Thesefindings suggest that a digital-based Deep Learning and TaRLapproach effectively enhances students’ understanding andengagement in learning statistics.